2019
DOI: 10.5812/ijp.92193
|View full text |Cite
|
Sign up to set email alerts
|

Emotional State According to Breakfast Consumption in 62276 South Korean Adolescents

Abstract: Objectives: Adolescents frequently skip breakfast for a variety of reasons. We investigated associations between lifestyle, emotional state, and breakfast consumption in adolescents. Methods: Data from 62276 adolescents were derived from the 13th Korean Youth Risk Behavior Web-based Survey (KYRBS), conducting from June 1, 2017 to June 30. The adolescents were drawn by stratified multistage clustered samples from 400 middle schools and 400 high schools. Breakfast skipper was defined as those who ate breakfast l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…We also found some educational interventions [42,[46][47][48][49][50][51][52] and studies that focused on adherence to the Mediterranean diet [53,54]. Of special interest are those relating emotional state [55] or social support [56,57] with breakfast among adolescents. The scarcity of research on adolescent eating habits during the school day [16][17][18][19][20]56] justifies the relevance of this line of research and supports the need for policies that favour the creation of healthy environments.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We also found some educational interventions [42,[46][47][48][49][50][51][52] and studies that focused on adherence to the Mediterranean diet [53,54]. Of special interest are those relating emotional state [55] or social support [56,57] with breakfast among adolescents. The scarcity of research on adolescent eating habits during the school day [16][17][18][19][20]56] justifies the relevance of this line of research and supports the need for policies that favour the creation of healthy environments.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies show that girls tend to skip breakfast more frequently than boys, as well as older students as compared to younger ones [15,23,29]. This last fact is also widespread among those students whose parents have a higher educational level [55] and among those who do not perform physical activity [55].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies among adolescents or emerging adults found associations between skipping breakfast and overweight/obesity, 6,[10][11][12][13][14][15] more negative body perception 13 and unhealthy dietary behaviour, 16 including low fruit and vegetable intake, 1,13,16,17 higher sodium intake, 16 lower consumption milk/dairy, 1,11,16 higher consumption of sweets, sugary or soft drinks, 1,13 and skipping other meals. 11,13 Mental health correlates of skipping breakfast include stress or mentally distressed, [18][19][20] depressive mood, 10,18,[21][22][23] lower happiness scores, 24 suicidal behaviour, 10,18 shorter sleep duration, 1 nocturnal sleeping problems, 25 and poor sleep quality. 26 Skipping breakfast has among adolescents or emerging adults further been associated with substance use, such as smoking 1,12,27 and alcohol use, 1,10,12 physical inactivity 1,11,15,28…”
Section: Introductionmentioning
confidence: 99%
“…11,13 Mental health correlates of skipping breakfast include stress or mentally distressed, [18][19][20] depressive mood, 10,18,[21][22][23] lower happiness scores, 24 suicidal behaviour, 10,18 shorter sleep duration, 1 nocturnal sleeping problems, 25 and poor sleep quality. 26 Skipping breakfast has among adolescents or emerging adults further been associated with substance use, such as smoking 1,12,27 and alcohol use, 1,10,12 physical inactivity 1,11,15,28 and sedentary behaviour. 1,11 Other effects included poor oral hygiene, such as less frequent tooth brushing 29 and no dental care visit in the past year, 30 and poor hand hygiene, such as no hand washing before meals, 29 no seatbelt use, 29 cardio metabolic risk factors, such as systolic blood pressure, 5 and poorer academic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation